SP0119 The evolving role of mepolizumab in egpa. (12th June 2018) - Moosig, F.
Abstract : There is overwhelming evidence that eosinophiles play a key role in the pathogenesis of EGPA. Il-5 is the central cytokine for eosinophil maturation, eosinophil release from the bone marrow and eosinophil survival. Mepolizumab is an antibody neutralising IL-5, which proved efficient in the hypereosinophilic syndrome and eosinophilc asthma, amongst other conditions. Targeting this cytokine in EGPA therefore seemed plausible. Two small uncontrolled trials demonstrated the safety of mepolizumab in EGPA and indicated the potential for induction of remission, maintenance and steroid sparing. A randomised controlled trial (MIRRA) confirmed those findings and showed higher rates of accrued remission for mepolizumab when given as ad-on medication to conventional immunosupressants and/or glucocorticoids. Steroid sparing properties were also confirmed. MIRRA and previous trials in different indications issued no major safety concerns. Based on this trial drug approval for EGPA might be feasible. To date the major problems in the treatment of EGPA are 1) refractory disease 2) a high frequency of relapses and 3) the need for high glucocorticoid doses in many patients. Mepolizumab could be used for induction of remission in addition to glucocorticoids. However, its not yet clear, which subgroup of patients might profit most. Especially patients with severe disease have not been investigated. For patients with refractors non-severe disease mepolizumab is a potential option. Mepolizumab also was efficient in preventing relapses and therefore may also be used for maintenance of remission, especially in patients suffering from prevalent relapses. Finally, patients with high need for glucococrticoids could profit from mepolizumab, particularly in case of steroid-sensitive comorbidities or steroid-induced complications. Disclosure of Interest: F. Moosig Consultant for: Chugai, GSK